Financial ratio in assessing the financial performance of the company PT.Golden Energy Mines, Tbk - Dessy Dessy Evianti; Rachmawaty Rachman; Muhammad Yusuf; Mutia Adinda Lesmana (Institute of Computer Science (IOCS), 2023)
. Golden Mines Energy, Tbk is one _ companies operating in the field sector coal mining . Study This aim For describe , analyze and know performance finance PT.Golden Energy Mines Tbk which was founded in 2011. Problems studied about condition finance and performance finance PT. Golden Energy Mines, Tbk for 6 years start period 2017 - 2022. Data used is secondary data form report existing finances _ published on the Indonesian Stock Exchange for the period 2017 - 2022. Research This is study quantitative with measurements used _ use tool analysis form ratio finances include _ ratio liquidity , profitability , solvency and market value . Research results show ratio proxied liquidity _ with the company's current ratio and quick ratio in very good condition with The average current ratio (CR) value is 135.17% and the average quick ratio (QR) value is 127.77%. Ratio proxied profitability _ with a return on equity (ROE) reaching 59.26% and an average net profit margin (NPM) reaching 14.44%. And for ratio solvency proxied company _ with the debt to asset ratio (DAR) showing the average value is 54.84% whereas for debt to equity ratio (DER) reached average value 123.18%. And for ratio proxied market value with earnings per share (EPS) reaching average value Rp. 592.76,- per share the shares and the price earnings ratio (PER) reached the average level returns 6 times.